Ideation Factors on Long-Acting Reversible Contraception Practices Among Family Planning Clients - Handayani, Sarah; Suraya, Izza; Asiah, Nur; Majid, Nurkholis (jitek, 2022)
Ideation is a new way of thinking involving the diffusion of these ideas through social interaction in local, culturally homogeneous communities. Making decisions about behavior depends on ideation factors. This study aimed to determine ideation factors associated with long-acting contraceptive behavior among family planning (FP) clients in East and North Jakarta. The data was derived from the "My Choice District Mini-Survey" conducted in East and North Jakarta between November and December 2016. The sample involved 720 women from both districts using a multi-stage cluster sampling process. An ideation factor was constructed from knowledge, attitude, social support, and interpersonal discussion on "Long Acting and Reversible Contraception" (LARC). A logistic regression analysis was performed to identify the most dominant factors associated with long-acting contraceptive behavior. This study found that the number of family planning clients who used LARC was 223 (30%). Of the percentage of using LARC attributed to each ideational score, the highest was 47%, and the lowest was 11%. The knowledge of LARC that can be used for spacing was the strongest ideation variable with Adjusted Odds Ratio (AOR) = 4.55 (95% CI = 3.13 -6.61; p-value =0.000); followed by limiting with AOR 3.46 (95% CI 1.61 - 7.45; p-value= 0.001). The study confirmed the correlation between ideation factors on LARC and its use. To increase the number of LARC users, we should improve the supply side program by increasing FP clients' knowledge about LARC and shifting attitudes on LARC into positives.